Factors Affecting Work Stress on Nurse Performance in the Covid-19 Isolation Inpatient Room - Suci Sofiyanti Mochtar; Arifah Devi Fitriani; Jitasari Tarigan Sibero (Journal La Medihealtico, 2022)
The low performance of nurses is caused by work stress experienced by nurses. The results of the initial survey with 10 nurses found that as many as 7 nurses experienced symptoms of work stress on nurses. This study was to determine the effect of work stress factors on nurse performance. This research is a quantitative study with a cross sectional study, September-October 2021. Total population sample. Survey data were analyzed using the Chi Square test and logistic regression. Univariate research results from 42 respondents, most of the respondents were aged 36-45 years, namely 25 (59.5%), female sex as many as 27 (64.3%) and had a D3 degree in Nursing education, namely 25 (59.5%) ) respondents. The results of bivariate analysis showed that there was an effect of communication (p=0.000), saturation (p=0.014), appreciation and recognition (p=0.006), conflict (p=0.006), income (p=0.001), family (p=0.001 ), workload (p=0.000), job relocation (p=0.023) on nurse performance. The multivariate results showed that the variable that had the most influence on the performance of nurses in the covid-19 isolation inpatient room at TK III Reksodiwiryo Padang Hospital in 2021 was the workload variable (p=0.003, OR = 21.747 (95% CI = 2.879-163.264). The conclusion is that all variables, namely communication, saturation, appreciation and recognition, conflict, income, family, workload, job relocation, have an influence and the most influential variable is workload. Suggestions as input in evaluating nurse performance as well as a basis for making a policy to improve nurse performance.